Determinants, Efficiency and Wealth Effects of Malaysian Corporate Mergers and Acquisitions - Jaaman, Saiful Hafizah (2007)
This research analyses four important issues pertaining to merger and acquisition (M&A) announcements in Malaysia to the bidder and target firms, namely the effects on shareholder's wealth, firm's financial performance pre and post M&A, effects of firm's characteristics on shareholder's wealth and the determinants of shareholder's wealth. Taking into account the two distinguished economic backdrops, this study segregates M&A announcements into two sub-periods; the booming period of 1985 to 1994 and the period surrounding the financial crisis, from 1995 to 2001. Bidder and target firms are classified into the finance and non-finance sectors and the bidder firms are further categorised to bidders announcing to acquire listed target firms and bidder firms that announce to acquire non-listed targets. Employing the event study methodology, findings on the wealth effects provide evidence that the target firms do not benefit from M&A activities, regardless of classifications and sub-periods. M&A activities in the period 1985 - 1994 benefit bidder firms from the non-finance sector that acquire listed target firms while M&A activities in the period 1995 - 2001 significantly profit bidder's shareholders in the non-finance sector that acquire non-listed target firms. The regression analyses results are consistent with results reported in the literature that show profitability measures to be the main factors in determining abnormal returns. Generally, findings of this study show that during the booming economy of 1985 to 1994, M&A is not the growth strategy chosen by firms. The enhanced values of bidders that acquire listed target firms indicate that M&A is mainly done to capture larger market shares or to create monopolies. In Malaysia, M&A is considered more as the strategy to survive as depicted by the high merger announcements in the period of 1995 to 2001 when the economy is in turmoil. Though the forced merger scheme is a necessary measure taken at the time, findings of this study prove that enforced merger scheme destroys value of both bidder and target firms listed in the finance sector.